Meningitis due to Bacillus cereus: A Case Report and Review of the Literature. Issue 1 (2012) - Stevens, Michael P; Elam, Kara; Bearman, Gonzalo
Abstract : Bacillus cereus is infrequently associated with invasive central nervous system (CNS) disease. Infection is associated with conditions that lead to reduced host immunity and provide direct access to the CNS, such as spinal anesthesia and ventricular tubes and shunts. A case of ventriculitis secondary to B cereus in a patient receiving intrathecal chemotherapy is reported, along with a review of the current literature. B cereus can colonize medical devices, thus posing a risk for invasive disease. Despite aggressive treatment with broad-spectrum anti-infectives, the mortality of CNS invasive B cereus is high. Clinicians should not dismiss Gram-positive rods resembling Bacillus species from normally sterile sites as contaminants in critically ill patients. Appropriate antibiotic therapy should be promptly initiated to limit morbidity and mortality.